Intersectionality of Patriarchy and Colonialism: A Postcolonial Ecofeminist Reading of Sahar Khalifeh’s The End of Spring - Rashed Daghamin (Acta Scientiarum. Language and Culture, 2025)
This essay examines the postcolonial ecofeminist implications of The End of Spring (2008) by Sahar Khalifa, a Palestinian nationalist and feminist. Palestinian women are confronted with a dual burden of disabling discourses: the master narrative of the Israeli occupation and the masculine rhetoric of the colonized Palestinian man. The interpretations of the novel from a postcolonial ecofeminist perspective bolster the postcolonial ecofeminist argument that the Israeli exploitation and occupation of Palestinian land and the double oppression and marginalization of Palestinian women are intertwined within patriarchal and colonial systems. The treatise highlights the maternal and physical contributions made by women to Palestinian liberation and resistance project and how the masculinization of the Palestinian resistance obstructs the liberation project and hampers Palestinian nationalistic objectives. Khalifeh emphasizes the resistance of women against patriarchal and colonial forces in The End of Spring, as evidenced by the resolute perspectives of Umm Suad and Suad, her daughter. The participation of these two females in acts of resistance demonstrates that motherhood and the idea of a motherland, particularly in a struggle against patriarchal norms and colonialist power, are not anti-feminist but complementary and compatible with feminism.